Potential Role of Phospholipases in Virulence and Fungal Pathogenesis - Ghannoum, Mahmoud A. (American Society for Microbiology, 2000)
Microbial pathogens use a number of genetic strategies to invade the host and cause infection. These common themes are found throughout microbial systems. Secretion of enzymes, such as phospholipase, has been proposed as one of these themes that are used by bacteria, parasites, and pathogenic fungi. The role of extracellular phospholipase as a potential virulence factor in pathogenic fungi, including Candida albicans, Cryptococcus neoformans, and Aspergillus, has gained credence recently. In this review, data implicating phospholipase as a virulence factor in C. albicans, Candida glabrata, C. neoformans, and A. fumigatus are presented. A detailed description of the molecular and biochemical approaches used to more definitively delineate the role of phospholipase in the virulence of C. albicans is also covered. These approaches resulted in cloning of three genes encoding candidal phospholipases (caPLP1, caPLB2, and PLD). By using targeted gene disruption, C. albicans null mutants that failed to secrete phospholipase B, encoded by caPLB1, were constructed. When these isogenic strain pairs were tested in two clinically relevant murine models of candidiasis, deletion of caPLB1 was shown to lead to attenuation of candidal virulence. Importantly, immunogold electron microscopy studies showed that C. albicans secretes this enzyme during the infectious process. These data indicate that phospholipase B is essential for candidal virulence. Although the mechanism(s) through which phospholipase modulates fungal virulence is still under investigations, early data suggest that direct host cell damage and lysis are the main mechanisms contributing to fungal virulence. Since the importance of phospholipases in fungal virulence is already known, the next challenge will be to utilize these lytic enzymes as therapeutic and diagnostic targets.